Análise morfofuncional e imuno-histoquímica das células de Leydig e dos macrófagos testiculares em ratos, após a exposição à nicotina durante as fases pré-natal e de lactação - Paccola, Camila Cicconi [UNIFESP] (2010)
Nicotine is largely consumed by worldwide people since it is a component of cigarettes. It reaches the maternal milk and is able to cross the placental membrane. Nicotine induces apoptosis in different cell types and interferes with endocrine functions. Reproductive side effects of this drug, such as testicular atrophy, erectile dysfunction and male infertility were also described. Nicotine suppresses testosterone secretion in adult male rats. Testosterone is produced from cholesterol and is synthesized by Leydig cells, with participation of the testicular resident macrophages, which are important for post-natal Leydig cell development. These data raised the hypothesis that the testicular damage induced by nicotine could be mediated by alterations or even apoptosis of Leydig cells. Because macrophages are also involved in testosterone synthesis and Leydig cell development, it is reasonable to consider the role of these cells in the nicotine-induced testicular damage. Given the complex testicular paracrine regulation, it is probable that such alterations induce germ cell damage in the post-natal phase. Thus, the aim of this study was to investigate whether the administration of nicotine to pregnant and lactating rats, in a dose equivalent to the consumption of one packet of cigarettes per day, provokes: a) alterations of cholesterol and sexual hormone levels in the plasma and in the testis; b) morphological and numerical alterations of Leydig cells and testicular macrophages. For this, 22 rats were treated with nicotine during pregnancy and lactation. Nicotine was administrated using an osmotic minipump calibrated in way to release 2mg/Kg/day of nicotine (equivalent to the consumption of 20 cigarettes/day). The minipump was implanted subcutaneously at the first day of pregnancy and replaced just after birth (lactation period). The second minipump was removed at the weaning day (22dpp). Minipumps without nicotine were implanted in other 22 pregnant and lactating rats (Sham group) with the aim to check the innocuousness of this procedure. More 22 pregnant and lactating rats did not receive any treatment or manipulation (Control group). The male pups of each offspring were distributed in 4 subgroups according to the age of euthanasia (1, 30, 60 and 90dpp). The testes were submitted to biometric analysis (weight and volume) after what they were processed for histopathological study (historesin and paraffin sections/PAS+H) and immuno-detection of adult Leydig cell (anti-11â-HSD type 2) and resident macrophages (anti-ED2). The numerical densities of Leydig cells and ED2+ macrophages were obtained using the Leica Q-Win image analysis system. Plasma levels of cholesterol and testosterone (all ages) and estrogen (30, 60 and 90 dpp) as well as intratesticular cholesterol and testosterone (60 and 90 dpp) were investigated. Plasma, urine and milk cotinine and nicotine levels were obtained at 22ddp by chromatography. The results showed that nicotine provoked decrease of body weight (p<0.05) and cholesterol plasma level (p<0.05) at (1dpp), besides the suggesting reduced lipids in the fetal Leydig cells cytoplasm. Decrease of testicular weight and volume occurred at 30dpp (p.0.05) but not at 60dpp and 90dpp. At 60 and 90dpp, the nicotine-treated rats showed increase of body weight and at 90dpp the nicotine-treated rats show increased in plasma cholesterol and testosterone levels (p<0.05). Although no alterations of the numerical densities of macrophages and Leydig cells were observed, the histopathological analysis showed that, at 60 and 90dpp, there was an increase of the frequency of degenerating Leydig cells and a pronounced disorganization and sloughing of the seminiferous epithelium. At 90dpp a suggestive hypertrophy of Leydig cells was also observed, what parallels the increase of cholesterol and testosterone levels. At this age a suggestive increase of the frequency of meiotic anaphase and metaphase figures and Sertoli cell nuclei in the tubular lumen were also observed. Since a subtle reduction of the estradiol levels was observed at the three ages studied (30, 60 and 90dpp), it is possible to suggest that the action of nicotine in the testis caused Sertoli cell alterations. Finally, it was concluded that nicotine provokes a reduction of the offspring number, body weight and cholesterol plasma level when administered to females during the whole pregnancy period. It was also concluded that nicotine administration in rats during the whole pregnancy period and during lactation affects the metabolism of cholesterol and testosterone and leads to morphofunctional alterations of Leydig cells and of spermatogenesis in the adult offspring. On the other hand, this treatment does not cause quantitative alterations of Leydig cell and macrophage populations.